Influence of metro track parameters on vibration characteristics of vibration damping track. (December 2022) - Li, Xiang; Ma, Jie; Xu, Ning
In view of the abnormal wear of the vibration damping track with small radius curve on the subway, the vibration and noise problems associated with it have been widely concerned by society. The dynamic model of vehicle-track system including elastic damping track is established by using simulation software. The influence of structural parameters of steel spring floating slab track (SSFST) with small radius curve on the mode and vibration frequency, as well as the resonance characteristics of elastic track structure are analyzed. The results show the following: (1) Increasing the length of floating slab can effectively reduce natural frequency, while the range of frequency variation caused by the thickness of floating slab is relatively small. The length and thickness of floating slab can be properly adjusted to avoid the track resonance. (2) It is more integrated for the rail and floating slab through increasing the vertical stiffness of fastener, which increases the vibration frequency of the track structure. There is little effect on the vibration characteristics of SSFST for changing the installation spacing of steel springs. (3) It is more obvious for resonance to occur between the inner rail and floating slab at 116 Hz, 130 Hz and 161 Hz, and the track vibration mode shows multi-step reverse vibration on both sides and overall vertical bending vibration. (4) Due to the unbalance load caused by curve superelevation, the inner wheel weight plays the restraining role, which makes the inner rail and floating slab have various forms of bending deformation in a certain frequency range, increasing the complexity of the bending deformation of the track structure.